Underutilization of India’s trained science and technology workforce: Impact on gender disparity - Jugran, Arun K.; Sardana, Neha; Fatima, N. Nishad; Maheshwary, Sugandha; Sengupta, Durba; Chakravorty, Nishant (Proceedings of the Indian National Science Academy, 2025)
The growing STEM workforce of India faces remarkable underutilization, mostly among women and early-career researchers. A survey was conducted among 106 research professionals showed that 46% of the respondents experienced career breaks while only 20–22% perceived sufficient employment opportunities across educational levels. Gender disparity has become a remarkable, associated factor, influenced by and perpetuating the underutilization of the workforce, shaped by career interruptions associated to marriage, childbirth, and societal norms, which disproportionately affect 65% of women respondents. While over 50% respondents showed their interest in developing entrepreneurship, awareness of government schemes such as Startup India and Skill India remains inadequate. The findings from the study supports the short-term actions like childcare support and flexible re-entry policies, medium-term incorporation of entrepreneurship programs with scientific careers, and long-term development of R&D through increased investment and mentorship programs. Addressing systemic and gender-based obstacles is vital for optimizing scientific workforce and promoting development driven by innovation in India. Additionally, the promotion of scientific entrepreneurship and start-up schemes is essential for boosting research sector growth. Addressing the systemic barriers and supporting gender equity in science and academia can help India fully leverage its qualified STEM talent.